Penerapan Aplikasi Jamsostek Mobile (JMO) Pada Badan Penyelenggara Jaminan Sosial Ketenagakerjaan Bogor-Cileungsi - Sarah Dinda Hanifa; Nida Handayani (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
The JMO application is a digital-based social security service system in the form of mobile apps. In its application, the JMO application still has many problems, one of which is when logging into the JMO application, you still have to wait a few moments to enter the menu display, in the data updating feature, especially at the stages of biometric verification and system development, but it does not provide significant changes in terms of both features and application view. The research aims to see the application of the Jamsostek Mobile (JMO) application system to BPJS Ketenagakerjaan at the Bogor Cileungsi branch office. the research method used is qualitative with a descriptive approach. Data collection techniques used are observation interviews and documentation. Research using the theory of DeLone & McLean.